PENDAMPINGAN SPT BADAN PADA PERUSAHAAN YANG TERGABUNG DALAM GABUNGAN PENGUSAHA SUKU SAKAI RIAU (GAPENSUS) - Siregar, Inova Fitri; Rasyad, Rinayanti; Suci, Afred; Onasis, Dini (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This Community Service is carried out with the aim of providing a better understanding to the community about the procedures for filling out and submitting Corporate Tax Returns (SPT). With the assistance, it is hoped that it can reduce errors in filling out Corporate Tax Returns that can result in sanctions or fines for taxpayers, this is because many owners or managers of small companies have limited knowledge of taxation rules, including how to fill out and file Corporate Tax Returns correctly and small companies usually have limited resources, including in terms of finance and labor. This can make it difficult for them to fill out the Corporate SPT properly and on time.The activity method in this community service program is training and mentoring. Community Service Partners are members who are members of the Sakai tribal entrepreneurs association. This community service activity has been able to increase understanding and ability in the procedures for filling out and submitting Corporate Tax Returns (SPT).The results of community service activities that have been carried out broadly include several components, namely the success of the target number of training participants, the achievement of the planned material target, the achievement of training objectives and the ability of participants to master the material. The achievement of the target number of participants can be seen from the number of participants targeted was 10 people and in fact the activity was attended by 10 people so that the target number of participants could almost be met. All participants were able to follow the entire simulation process from start to finish, 100% of the designed activities were carried out, and 100% team readiness attendance. The target of delivering simulation material was also achieved because the material could be delivered as a whole.